KETEGUHAN IMAN DANIEL SEBAGAI FONDASI KETAHANAN MENTAL ANAK DI ERA MEDIA SOSIAL: PERSPEKTIF TEOLOGI ANTROPOLOGI - Epi Epi; Anisa; Anggi Enjelina (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research is motivated by the identity crisis phenomenon in children during the social media era, triggered by dependence on external validation and cyberbullying threats that adversely affect mental health. The primary objective to analyze how Daniel's exemplary faith through the principles of Imago Dei can be the foundation for children's mental resilience in facing digital pressures. The methodology employed is qualitative with an interpretive approach through literature studies and biblical analysis. Results indicate that the Imago Dei concept provides a stable identity foundation because a child's dignity is rooted in their status as God’s creation, not in digital metrics such as likes. Daniel’s example offers a practical model where steadfast faith and spiritual discipline preserve identity amidst external cultural assimilation. Integrating values of love, truth, and justice functions as an effective coping mechanism to protect children from social comparison and cyberbullying. In conclusion, an identity rooted in a relationship with God produces mental resilience that is not easily shaken by the fluctuation of online responses.